Literature Review of Analysis of The Reputation of Public Accounting Firms as Influenced by The Quality of Audit Results, Ethics, Integrity, and Auditor Experience - Nanditya Andini; Cris Kuntadi; Rachmat Pramukty (Sean Institute, 2025)
Literature Review article Analyzing the Reputation of Public Accounting Firms Affected by the Quality of Audit Results, Ethics, Integrity, and Audit Experience is a scientific article that builds research hypotheses between variables used in further research. The method of writing this Literature Review article is to use the library research method, which is sourced from online media such as Google Scholar and other academic online media. The results of this literature review article are: 1) The Quality of Audit Results affects the Reputation of the Public Accounting Firm; 2) Ethics affects the reputation of the Public Accounting Firm; 3) Integrity affects the reputation of the Public Accounting Firm; and 4) Auditor experience affects the reputation of the Public Accounting Firm.